Animal dietary exposure in the risk assessment of contaminants in feed - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract EFSA performs dietary exposure assessments for food‐producing and non‐food‐producing animals to deliver risk assessment for mandates on the presence of contaminants in feed. The CONTAM and FEEDAP Panels identified the need to update the animal dietary exposure assessment model used in those assessments in CONTAM Scientific Opinions since 2011 in cases where insufficient occurrence data are available on species specific compound feeds. The Panels proposed in this statement a series of model diets based on groups of feed materials with the possibility to use different feed materials in their formulation. The Panels considered that the currently proposed model diets cover the need of the CONTAM Panel to assess the dietary exposure of animals to contaminants in feed.